A novel approach to bi-objective optimization of touch-screen installation position for minimizing physical workload and increasing screen visibility. - Chihara, Takanori; Seo, Akihiko; Sakamoto, Jiro (Applied Ergonomics, 2019)
The aim of this study was to propose a new method for optimizing the touch-screen installation position in order to minimize the physical workload and increase screen visibility. Ten students participated in this study. The participants utilized a touch screen at different installation heights (50, 65, and 80% of stature), tilt angles (0°, 45°, and 90° from the horizontal plane), and having different button sizes (a square with a side of 10, 20, and 30 mm). The joint angles, when using a touch screen, were measured to calculate the joint torque ratios (JTRs). Subjective screen visibility were also determined. The optimal installation position was determined by solving a bi-objective optimization problem consisting of two objective functions. The Pareto optimal solutions for the two objectives showed a range of 1124-1251 mm and 44.4-67.9°. The proposed method determined the optimal installation position of the touch screens.